(3cJGH GdCTHGg hGdfXGFQs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ld Yf GdCTHGg hGdfXGFQ hOd Ydi WQb GdgOi HGdCbhGd GdUMjMI CeG HYO aEf GdYdhe hEf cGfJ JJYGXe TQakG GdcdGe ai GdbhGYO GdabgjI s
(3BNQgG (B:s
(3hCNUU Gddge GdUOjb hGdaGQhb hPG GdfhQjf hGdeQJVi HQVkG JGe dGjNJda Yf HbjI GdUMGHI hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdgG Jedcs
(3cJHJ GdYfGhjjf HGdMeQI HBNQgG hbajI HGSe GdSjO CMeO GdMSjfi Hf GdSjO CMeO GHf GdSjO jhSa GdMSjfi SfI (B1323(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3Gdabg GdESdGejs